2009
DOI: 10.1037/a0014653
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of gains following experiential therapies for depression.

Abstract: Follow-up data across an 18-month period are presented for 43 adults who had been randomly assigned and had responded to short-term client-centered (CC) and emotion-focused (EFT) therapies for major depression. Long-term effects of these short-term therapies were evaluated using relapse rates, number of asymptomatic or minimally symptomatic weeks, survival times across an 18-month follow-up, and group comparisons on self-report indices at 6- and 18-month follow-up among those clients who responded to the acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 51 publications
1
46
0
1
Order By: Relevance
“…This is achieved by exploring beliefs associated with the experienced emotion and by identifying the needs that can motivate change in personal meanings and beliefs. EFT trials showed promising results with respect to both acute response and subsequent prevention of depressive symptoms [5]. Despite these promising findings, no study is available so far on the utility of EFT in the treatment of BED associated with obesity.…”
Section: Tablementioning
confidence: 99%
“…This is achieved by exploring beliefs associated with the experienced emotion and by identifying the needs that can motivate change in personal meanings and beliefs. EFT trials showed promising results with respect to both acute response and subsequent prevention of depressive symptoms [5]. Despite these promising findings, no study is available so far on the utility of EFT in the treatment of BED associated with obesity.…”
Section: Tablementioning
confidence: 99%
“…Finally, interventions that focus on enhancing ER, such as emotion-focused therapy [46], dialectical behavioral therapy [47] and exposure-based cognitive therapy [48] have been shown to be effective in MDD [48,49,50,51,52,53,54]. …”
Section: Introductionmentioning
confidence: 99%
“…68 Similarly, a RCT of a 'coping with depression' psychoeducational group programme, with booster session up to 4 months after the intervention had finished, was effective in reducing depression at 6 months but not at 12 months. 69 In contrast, a RCT of CBT as an adjuvant therapy for treatment-resistant depression found that it was effective at the 6-and 12-month follow-up. 70 Ten therapist-delivered sessions of CBT over the internet were effective in reducing depression at 4 and 8 months (equivalent to our short-term measures).…”
Section: Structured Psychological Treatment Of Depression In Other Grmentioning
confidence: 99%